Renal haemangiosarcoma in an ox - M. Kemal Çiftçi; S. Serap Türkütanıt; Mustafa S. Uslu (Eurasian Journal of Veterinary Sciences)
Multifocal 0.5-1.2 cm., dark-red nodular masses were seen within the renal cortex of a ten- year old ox which slaughtered at munic ipal abattoir in Beyşehir. Microscopic examination of these renal masses cantirmed the presence of haemangiosarcoma in the kidney of ox.